Targeted Gene Addition of Microdystrophin in Mice Skeletal Muscle via Human Myoblast Transplantation - Basma F Benabdallah; Arnaud Duval; Joel Rousseau; Pierre Chapdelaine; Michael C Holmes; Eli Haddad; Jacques P Tremblay; Christian M Beauséjour (Elsevier, 2013)
Zinc finger nucleases (ZFN) can facilitate targeted gene addition to the genome while minimizing the risks of insertional mutagenesis. Here, we used a previously characterized ZFN pair targeting the chemokine (C-C motif) receptor 5 (CCR5) locus to introduce, as a proof of concept, the enhanced green fluorescent protein (eGFP) or the microdystrophin genes into human myoblasts. Using integrase-defective lentiviral vectors (IDLVs) and chimeric adenoviral vectors to transiently deliver template DNA and ZFN respectively, we achieved up to 40% targeted gene addition in human myoblasts. When the O6-methylguanine-DNA methyltransferaseP140K gene was co-introduced with eGFP, the frequency of cells with targeted integration could be increased to over 90% after drug selection. Importantly, gene-targeted myoblasts retained their mitogenic activity and potential to form myotubes both in vitro and in vivo when injected into the tibialis anterior of immune-deficient mice. Altogether, our results could lead to the development of improved cell therapy transplantation protocols for muscular diseases.